Evaluation of troponin T levels and cardiac findings of the children in pediatric intensive care with high proBNP levels - Ajda Mutlu Mıhçıoğlu; Esra Şevketoğlu (Trends in Pediatrics)
Objective: Pro-B type brain natriuretic peptide (proBNP) is released from cardiac ventricular myocytes as a result of increased volume and pressure. Troponin T plays a role in the contraction process. Both proteins may be elevated in many cardiac and non-cardiac conditions. Our aim is to evaluate troponin T values and cardiac findings of the patients in pediatric intensive care unit (PICU) with elevated proBNP levels.